Prevalence and Risk Factors of Nurse Work Stress During The Covid-19 Pandemic in Hospitals: Systematic Literature Review - Umi Fatikhatul Luthfiyah; Chriswardani Suryawati; Antono Suryoputro (Sekolah Pascasarjana Universitas Brawijaya, 2022)
The COVID-19 pandemic has significantly impacted the health sector. Nurses are always active participants in implementing COVID-19 Pandemic interventions during the pandemic. The shortage of nursing resources has an impact on the workload of nurses who are on the front lines of the pandemic. The increased workload will affect the nurse's work stress. The purpose of this article was to evaluate the prevalence of nurse work stress and the risk factors for nurse work stress in hospitals during the COVID-19 pandemic. The literature search was conducted between 2020 and 2022. The literature search was performed using the databases: PubMed, Science Direct, ResearchGate, Scopus, Proquest, Springer Link, and Cambridge. The search terms used are a factor; nurses; stress; the COVID-19 pandemic; hospital. Inclusion and exclusion criteria were also applied in the search for related research articles. Countries that experience high levels of work stress include Egypt, Indonesia, Korea, Tunisia, and Murat. Factors that cause nurse work stress can be classified into 3 main risk factors, namely: 1) Socio-Demographic, including age, gender, marital status, and work experience; 2) Behavior and Health, including social support, exposure to COVID-19 infection, the death at work; 3) Hospital Organization, covering workload, work shifts, burnout, education and training, availability of PPE. A systematic review of the risk factors for nurses' work stress during the COVID-19 pandemic is expected to be a reference material in determining mental health strategies for hospital human resources, especially among nurses. Keywords: nurse, work stress, the COVID-19 pandemic, hospital